How the Mind Understands Meaning: A Cognitive Semantic Approach - Daniel Daniel Saputra Gurning; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates how meaning is cognitively constructed through metaphor, image schemas, and semantic frames in English and Indonesian discourse. Employing a qualitative descriptive design, it analyzes 30 text samples from political, religious, educational, and digital communication contexts. Drawing on Conceptual Metaphor Theory (CMT), Image Schema Theory, and Frame Semantics, the findings demonstrate that meaning-making is embodied, culturally embedded, and contextually situated. Metaphors like Life Is A Journey and Argument Is War dominate across domains, while image schemas such as Container and Path underlie the cognitive organization of abstract concepts. Semantic frames further enrich meaning by activating situational knowledge structures. The results highlight that linguistic meaning is not fixed but shaped by socio-cultural experiences and cognitive structures.